Thank You for Hearing My Voice – Listening to Women Combat Veterans in the United States and Israeli Militaries - Daphna-Tekoah, Shir; Harel-Shalev, Ayelet; Harpaz-Rotem, Ilan (Frontiers in Psychology, 2021)
The military service of combat soldiers may pose many threats and often take a toll on body and mind, influencing the physical and emotional well-being of combatants and veterans. The current study aims to enhance our knowledge about the combat experiences and the challenges that female soldiers face both during and after their service. The study is based on qualitative methods and narrative analysis of in-depth semi-structured personal interviews with twenty military veterans. It aims to analyze the narratives of American and Israeli female combat soldiers regarding their military service, with emphasis on the soldiers’ descriptions, in their own words, about their difficulties, challenges, coping and successes during their service and transition to civilian life. A recurring theme in the interviews with the veterans of both militaries was the need to be heard and the fact that societies, therapists, and military institutions do not always truly listen to female veterans’ experiences and are not really interested in what actually ails them. Our research suggests that conventional methods used in research relating to veterans might at times be inadequate, because the inherent categorization might abstract, pathologize, and fragment a wide array of soldiers’ modes of post-combat being. Moreover, female veterans’ voices will not be fully heard unless we allow them to be active participants in generating knowledge about themselves.